METHODS OF DETECTION OF SPECIFIC ANTIBODIES IN BRUCELLOSIS - Djabbarova N.R.,; Daminov F.A.,; Xolmatova D.,; Rustamova F., (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Plate Agglutination Reaction (Heddleston Reaction). The advantage of this method is the simplicity of setting up the reaction, quick results, and the sensitivity of the reaction. A single brucellosis diagnosticum is used as an antigen to perform the Heddleston and Wright reactions. In the case of a positive reaction, flakes (agglutinate) appear in the drops of serum containing  the antigen in the very first minutes. The maximum observation period is 8 minutes. For the diagnosis of brucellosis, only a positive result of the reaction is important. In cases of uncertain or negative results, along with epidemiological or epizootic indications, or in hospitals and donor screenings where it is necessary to determine the titer of agglutinins and their dynamics, the Wright, Coombs, Passive Hemagglutination Reaction (PHAR), and Enzyme-Linked Immunosorbent Assay (ELISA) should be used [1,4,6,8,9].